1937
DOI: 10.2134/agronj1937.00021962002900120004x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Resistance to Loose and Covered Smuts in Oat Hybrids1

Abstract: R ESULTS on the inheritance of smut resistance in crosses between Mar kton and certain other oat varieties were reported in a previous paper. 3 Markton is very resistant to the specialized races of both loose smut (Ustilago avenae (Pers.) Jens.) and covered smut (U. levis (K. and S.) Magn.), that have been used by the senior author in his experiments. Of the other varieties used as parents, Canadian, Early Champion, and Victor are susceptible to both smuts, Gothland is susceptible to loose smut but resistant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1941
1941
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The cultivars AC Medallion, AC Assiniboia, AC Belmont, and AC Preakness are assumed to have the Markton resistance based on their pedigree (D. Brown, Cereal Research Centre, personal communication). Virulence on the Markton resistance genes (Markton may carry three genes for resistance; Murphy and Coffman 1961;Reed and Stanton 1938) has been reported only once from Oregon (Smith and Bressman 1931). Cultivar AC Lotta was also resistant to all but one oat smut collection from 1995-1999 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cultivars AC Medallion, AC Assiniboia, AC Belmont, and AC Preakness are assumed to have the Markton resistance based on their pedigree (D. Brown, Cereal Research Centre, personal communication). Virulence on the Markton resistance genes (Markton may carry three genes for resistance; Murphy and Coffman 1961;Reed and Stanton 1938) has been reported only once from Oregon (Smith and Bressman 1931). Cultivar AC Lotta was also resistant to all but one oat smut collection from 1995-1999 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Roussel}] of oat (Avena sativa L.) are controlled through the widespread utilization of resistant cultivars and fungicide seed treatments (Thomas 1995). The highly effective resistance in most oat cultivars grown in western Canada is derived from Markton, which may carry three genes for resistance (Reed and Stanton 1938;Murphy and Coffman 1961). Until 1996, carbathiin was the only fungicide active ingredient registered for use as a seed treatment on oats in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…357-1) in the early 1920s] was a selection from an unnamed Turkish line (Holton & Murphy 1966) and may carry three genes for resistance (Murphy & Coffman 1961). Studies by Reed and Stanton (1938) suggested that resistance to U. avenae in Markton is determined by two genes, while resistance to U. kolleri is determined by one gene. They did not determine if the gene for resistance to U. kolleri was the same as one of the genes for resistance to U. avenae.…”
Section: Resultsmentioning
confidence: 99%